Språkstadieordböcker nu och då - Djärv, Ulrika (Nordiske Studier i Leksikografi, 2006)
Period dictionaries past and present. This paper deals with the typological distinction of synchrony and diachrony in period dictionaries, particularly K.F. Söderwall’s Ordbok öfver svenska medeltidsspråket (Sdw) (1884-1918). First of all the established definitions of the lexicographic terms synchronic and diachronic are given. Then follows an argument for a different set of concepts regarding the descriptive methods in period dictionaries: either describing the language as a system or focusing on the changes it undergoes (essentially regardless of the length of the period). These concepts are also – with some hesitation – labelled as synchrony and diachrony respectively. In order to concretise these concepts, different synchronic and diachronic descriptive methods applicable to different information categories in period dictionaries are presented. Finally, an article in Sdw is briefly discussed. This article does not strongly demonstrate the use of either a synchronic or a diachronic descriptive method.